Joe Bradley - Dunham, Carroll 1949- (Albright-Knox Art Gallery, 2017)
American painter Joe Bradley has distinguished himself among the artists of his generation with his mutable approach to art-making. With minimal fuss, Bradley works in series, picking up and discarding styles and oscillating between abstraction and figuration as it suits him. 'A retrospective of his work would look like a group show,' wrote dealer and collector Kenny Schachter. Bradley's first large-scale North American exhibition supports this observation: he is shown moving from expressionistic canvases that record the detritus and spontaneity of the studio environment to subtly figurative send-ups of Minimalist painting, then to starkly primitivistic glyphs drawn in grease pencil on unprimed canvas, followed by modular aluminum sculptures paired with textual directives
Published on the occasion of the exhibition "Joe Bradley", Albright-Knox Art Gallery, June 24-October 1, 2017; Rose Art Museum, Brandeis University, October 15, 2017-January 28, 2018
Keywords: Bradley, Joe -- 1975-; Bradley, Joe / 1975- / Exhibitions; Painting, Abstract / 21st century / Exhibitions; Drawing, American / 21st century / Exhibitions; Illustrated works; Interviews; Ausstellungskatalog; Ausstellungskatalog -- Albright-Knox Art Gallery -- 24.06.2017-01.10.2017 -- Buffalo, NY; Ausstellungskatalog -- Rose Art Museum -- 15.10.2017-28.01.2017 -- Waltham, Mass